Implementasi Metode Storytelling dalam Pembelajaran Akidah Akhlak di MTs Darul Quran Pekanbaru - Akbar, Rahmadani (Tarunaedu: Journal of Education and Learning, 2026)
This study aims to describe the implementation of the storytelling method in teaching Akidah Akhlak at MTs Darul Qur'an Pekanbaru, as well as to analyse the supporting and inhibiting factors and their implications for the learning process and outcomes. The background to this study is based on the need for innovative teaching methods that not only address cognitive aspects but also affective aspects and character building in students. This research uses a qualitative approach with data collection techniques through in-depth interviews with Akidah Akhlak teachers and documentation studies. The results show that the storytelling method is applied by inserting Islamic stories relevant to the material, delivered in a communicative, expressive, and persuasive manner so as to attract students' attention and foster a deeper understanding of religious values. Supporting factors for the application of this method include teachers' communication skills and the religious culture of the madrasah, while obstacles include time constraints and student character variations. Storytelling has been proven to have positive implications for improving religious concept understanding, moral value internalisation, learning motivation, and the pedagogical relationship between teachers and students. Thus, storytelling is an effective and relevant method to be applied in Akidah Akhlak learning, particularly in fostering students' moral and spiritual awareness.